2022
DOI: 10.3390/en15124482
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Production through Acid Catalyst In Situ Reactive Extraction of Chlorella vulgaris Foamate

Abstract: A method of biodiesel production from the freshwater microalgae Chlorella vulgaris based on the conversion of the dewatered algal biomass from a foam column (“foamate”) was investigated. The foam column collected and concentrated the microalgae. The foam was generated by passing air through a pool of algae, to which a collector/surfactant cetyltrimethylammonium bromide (CTAB) had been added. To produce biodiesel, the resultant “foamate” was esterified in situ using sulfuric acid and methanol. The effect of rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 56 publications
(79 reference statements)
0
2
1
Order By: Relevance
“…The GC–MS result of the current study was higher than the findings of Najjar et al (Najjar et al 2021 ) who reported obtained GC–MS amount of biodiesel from cooking oil was 83.08%. Similarly, it was also higher than the results reported by Al-Humairi et al (Al-Humairi et al 2022 ) who obtained the maximum biodiesel yield (96 ± 0.2%). In the current study, the FAME content of algal biodiesel was methyl palmitate (32.1%), methyl heptadecanoate (11.2%), methyl myristate (8.2%), methyl lineolate (29.8%), methyl stearate (6.2%), methyl 10-heptadecanoate (7.7%) and methyl hexanoate (3%).…”
Section: Discussioncontrasting
confidence: 46%
“…The GC–MS result of the current study was higher than the findings of Najjar et al (Najjar et al 2021 ) who reported obtained GC–MS amount of biodiesel from cooking oil was 83.08%. Similarly, it was also higher than the results reported by Al-Humairi et al (Al-Humairi et al 2022 ) who obtained the maximum biodiesel yield (96 ± 0.2%). In the current study, the FAME content of algal biodiesel was methyl palmitate (32.1%), methyl heptadecanoate (11.2%), methyl myristate (8.2%), methyl lineolate (29.8%), methyl stearate (6.2%), methyl 10-heptadecanoate (7.7%) and methyl hexanoate (3%).…”
Section: Discussioncontrasting
confidence: 46%
“…Supercritical methanol with oxide catalysts, is another heterogenous catalyst, having supercritical methanol in conjunction with oxide catalysts (α-Al2O3) has shown to enhance the yield of fatty acid methyl esters (FAMEs), suggesting that complete dewatering of Chlorella vulgaris biomass may not be necessary. This method promotes higher liquid product and FAME yields, highlighting its potential for one-pot biodiesel production [78]. Table 2 provides a summary of the various catalysts used for biodiesel generation from Chlorella vulgaris, focusing on their reaction conditions and yields.…”
Section: Transesterification For Biodiesel Production and Catalystsmentioning
confidence: 99%
“…The ability to skip the cell disruption and extraction steps is advantageous in terms of both operating cost and energy consumption. Table 1 shows the research that has used this technique for FAME (biodiesel) production in recent years, highlighting the presence of microalgae [44][45][46][47][48][49].…”
Section: Transesterificationmentioning
confidence: 99%